4(-4a-3)=36

Simple and best practice solution for 4(-4a-3)=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(-4a-3)=36 equation:


Simplifying
4(-4a + -3) = 36

Reorder the terms:
4(-3 + -4a) = 36
(-3 * 4 + -4a * 4) = 36
(-12 + -16a) = 36

Solving
-12 + -16a = 36

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + -16a = 36 + 12

Combine like terms: -12 + 12 = 0
0 + -16a = 36 + 12
-16a = 36 + 12

Combine like terms: 36 + 12 = 48
-16a = 48

Divide each side by '-16'.
a = -3

Simplifying
a = -3

See similar equations:

| x-1.24=1.9 | | x+2.4=4.1 | | 4(x-7)=39 | | 6z-29=3z-8 | | 3(3x-3)y=32 | | 6c-17=3c-35 | | 9z-24=5z-8 | | 60=13m+a | | 4x+6=-x+36 | | logE=17.8 | | 6y-5x-5=6(xy)-5 | | (-3a-b)+(2a-5b)= | | 8888=500 | | 2-3y=px | | 18-Y=(-18) | | 10z-93=4z-45 | | 4g-11=13-2g | | 5a+6=3a+10 | | y-13=36 | | 3(4f-7)=-45 | | 10x^(1/3)-10x | | 8-5q=23 | | 5x+11=2x+38 | | -1+6c=11 | | -8+9c=10 | | 9x+13=4x+48 | | 17x+5=56 | | -9b+2=-7 | | 6x-1+6x=7 | | -5b+8=-32 | | 3x+py=6 | | 2x+4.1=3.9 |

Equations solver categories